The short-term efficacy of adventitial inversion with graft eversion anastomosis for the reconstruction of the aortic sinus in the root treatment of aortic dissection - Gao, Feng; Shi, Zepeng; He, Xuezhi; Gao, Yang; Zhuang, Xijing; Shi, Lei; Wang, Wenjun; Liu, Wei (Frontiers in Cardiovascular Medicine, 2022)
Background: The surgical approaches for a mildly affected aortic sinus (AS) are varied and controversial. We reconstructed the AS using extended adventitial inversion with graft eversion anastomosis (eAIGEA) and compared its perioperative difference and short-term efficacy with aortic wall wrapping vascular grafts and a right atrial shunt (AWrAS) technique in this study, thereby providing a new basis for surgical management strategies. Method: A total of 101 patients with mildly affected AS were enrolled in the clinical trial. Primary endpoints: reoperation-related events and aorta-related fatal events. Secondary endpoints: surgery-related duration and structural changes in the aortic root. Cardiac ultrasonography and aortic computed tomography angiography were performed before, two weeks after, and one year after surgery, respectively. Results: Compared with the AWrAS group (n = 56), the eAIGEA group (n = 36) had a significantly shorter surgery duration (the time from skin incision to skin closure) and a reduced time from shutdown to skin closure (P < 0.05). The cardiac ultrasonography performed in the follow-up patients at 12 months after surgery and 2 weeks after surgery showed a significant increase in the diameter of the aortic sino-tubular junction of the AWrAS group (n = 50) (P < 0.05). The eAIGEA (n = 33) method was better than the AWrAS technique concerning the persistence of the false lumen closure effect, anastomotic leakage, and aortic valve reduction (P < 0.05), and there was a significant difference between the two groups regarding the incidence of reoperation-related events (P < 0.05). Conclusion: Compared with the AWrAS technique, eAIGEA could shorten the operation time and prevent near-term dilation of the sino-tubular junction, with better safety and short-term surgical effect.